2018
DOI: 10.1007/s00540-018-2506-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting EZH2 rescued bupivacaine-induced neuronal apoptosis in spinal cord dorsal root ganglia in mice

Abstract: EZH2 is upregulated, whereas inhibiting EZH2 exerted rescuing effect in anesthetics (bupivacaine)-induced spinal cord DRG. The possible downstream target of EZH2 inhibition may interact with caspase and TrkC signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…These results indicated that the epigenetic histone posttranscriptional modification plays a significant role in the apoptosis of brain cells in stroke or ischemia/reperfusion injury. This was in conformity with previous studies indicating that the inhibition of EZH2 counteracts neuronal apoptosis in the spinal cord dorsal root ganglia in vivo 45 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicated that the epigenetic histone posttranscriptional modification plays a significant role in the apoptosis of brain cells in stroke or ischemia/reperfusion injury. This was in conformity with previous studies indicating that the inhibition of EZH2 counteracts neuronal apoptosis in the spinal cord dorsal root ganglia in vivo 45 …”
Section: Discussionsupporting
confidence: 93%
“…This was in conformity with previous studies indicating that the inhibition of EZH2 counteracts neuronal apoptosis in the spinal cord dorsal root ganglia in vivo. 45 In the present study, we provide evidence that EZH2-mediated H3K27me3 is involved in the epigenetic upregulation of PI3K/AKT/ mTOR signaling pathway during ischemic development. Studies reporting the implication of EZH2 in ischemic brain injury are scarce.…”
Section: Discussionsupporting
confidence: 55%
“…Both bupivacaine and ropivacaine are long-acting amide LAs. Administration of bupivacaine has been shown to induce neurological damage in a preclinical experimental rodent study [9,10]. Ropivacaine was developed after bupivacaine was noted to be associated with cardiac toxicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The CNC Networks predicted the interaction of numerous differentially expressed lncRNAs with three functional genes, including EZH2, Plod3, and SUV39H1. The inhibition of EZH2 activity was shown to suppress bupivacaine-induced neuronal apoptosis in spinal cord dorsal root ganglia [ 32 ]. Overexpression of the PLOD3 gene, which encodes a lysyl hydroxylase, significantly promotes the progression of gliomas and is associated with a poor prognosis in glioma patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%